Обґрунтування можливості забезпечення в ОЕС України процесів регулювання частоти відповідно до норм, визначених UCTE - Lenchevsky Ye.A.; Dubovskoy S.V. (General Energy Institute of the National Academy of Sciences of Ukraine, 2007)
Problem questions touching further development of system management in OES of Ukraine are considered. In particular, the questions of methodological approach development are considered near determination of frequency declining in power system depending on parameters and norms, accepted in UCTE. It is suggested to realize counteraction to arising up no balance power in a net, directed on his diminishing, by the centralized management (including or disconnecting) of the loading part of the AES stations specially selected for this purpose, that considerably changes existent principles of the primary adjusting and simplifies the process of adjusting. Possibility of providing in OES of Ukraine of processes of frequency adjusting is grounded under regulations set in UCTE.